Sleep-Related Hypermotor Epilepsy: Etiology, Electro-Clinical Features, and Therapeutic Strategies - Wan H (Dove Medical Press, 2021)
Huijuan Wan,1– 3,* Xing Wang,4,* Yiyi Chen,1,2 Bin Jiang,3 Yangmei Chen,5 Wenhan Hu,6 Kai Zhang,7 Xiaoqiu Shao1,2 1Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2China National Clinical Research Center for Neurological Diseases (NCRC-ND), Beijing, People’s Republic of China; 3Department of Neurology, First Affiliated Hospital, Xiamen University, Xiamen, People’s Republic of China; 4Department of Neurology, Chongqing University Central Hospital, Chongqing Emergency Medical Centre, Chongqing, People’s Republic of China; 5Department of Neurology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 6Beijing Neurosurgical Institute, Capital Medical University, Beijing, People’s Republic of China; 7Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoqiu ShaoDepartment of Neurology, Beijing Tiantan Hospital, Capital Medical University, No. 119 South 4th Ring West Road, Fengtai District, Beijing, 100070, People’s Republic of ChinaTel +86-135-5203-4066Email shaoxiaoqiu2000@aliyun.comAbstract: Sleep-related hypermotor epilepsy (SHE) is a group of clinical syndromes with heterogeneous etiologies. SHE is difficult to diagnose and treat in the early stages due to its diverse clinical manifestations and difficulties in differentiating from non-epileptic events, which seriously affect patients’ quality of life and social behavior. The overall prognosis for SHE is unsatisfactory, but different etiologies affect patients’ prognoses. Surgical treatment is an effective method for carefully selected patients with refractory SHE; nevertheless, preoperative assessment remains challenging because of the low sensitivity of noninvasive scalp electroencephalogram and imaging to detect abnormalities. However, through a careful analysis of semiology, the clinician can deduce the potential epileptogenic zone. This paper summarizes the research status of the background, etiology, electro-clinical features, diagnostic criteria, prognosis, and treatment of SHE to provide a more in-depth understanding of its pathophysiological mechanism, improve the accuracy in the diagnosis of this group of syndromes, and further explore more targeted therapy plans.Keywords: semiology, seizure onset zone, SOZ, epileptogenic zone, hypermotor, electroencephalogram